Providing the Competitiveness of Education due to the Formation of Professional Competence via the Project-Based Learning Technology - Zagirniak, Denys; Shalimova, Nataliia; Akmaldinova, Oleksandra; Stezhko, Yuri; Perevozniuk, Viktoriia (2021 IEEE International Conference on Modern Electrical and Energy Systems (MEES), 2021)
The paper highlights the innovative approach to providing the competitiveness of education. The idea of the productivity of project-based learning on the basis of integrative disciplines as a holistic reflection of the unity of professional and humanities knowledge in the scientific picture is presented. Academic disciplines are the integration of basic sciences at the applied level. Mathematical formalization, due to the high degree of generality of its apparatus, is recognized as the leading means of forming integrative content of educational competitiveness. The need for a new type of rationality is substantiated, which will provide the coordination of logic with the purpose of human existence and is able to combine rational and irrational forms of comprehension of reality and expand the scope of mathematical formalization. It is claimed that the decisive role in making a project decision belongs to the subject. A comparison of traditional and project-based learning according to the main criteria and practical advice on the areas of project implementation are presented.